Adaptive control of a general class of upper triangular systems with parametric uncertainty - Radom Pongvuthithum (2019)
© 2019 EUCA. This paper studies the problem of global adaptive control for a class of upper-triangular systems with nonlinear parameterization. We present sufficient conditions under which global adaptive stabilization is achievable by universal-type, gain-dependent nested saturation controllers. In the case of feedforward systems with unknown parameters, our control strategy leads to a new non-identifier based adaptive regulator that eliminates the use of switching adaptive gains, which is not only complicated and less intuitive but also results in discontinuous feedback control laws. Examples with simulation results are provided to validate the effectiveness of the proposed adaptive control method.